Molecular characteristics and phylogenetic analysis of Clostridium perfringens from different regions in China, from 2013 to 2021 - Zhong, Jia xin; Zheng, Hao ran; Wang, Yuan yuan; Bai, Lu lu; Du, Xiao li; Wu, Yuan; Lu, Jin xing (Frontiers in Microbiology, 2023)
Clostridium perfringens (C. perfringens) is a significant foodborne pathogen and a common cause of intestinal diseases in both animals and humans. Altogether, 186 isolates were obtained from humans (n = 147), animals (n = 25), and food (n = 14), comprising 174 type A strains (93.55%), 11 type F strains (5.91%), and one type D strain (0.54%); and were analyzed by multilocus sequence typing (MLST) and antimicrobial susceptibility testing. Additionally, some specific ST complexes were analyzed by cgMLST and cgSNP to investigate genetic relatedness. MLST indicated the most prevalent STs of C. perfringens of human and animal origin were as follows: ST221 (5/147), ST62 (4/147), ST408 (4/147), and ST493 (4/147) were predominant in humans, while ST479 (5/25) was the major type in animals. Within the same ST complex, genetically unrelated relationships or potential clustering/transmission events were further recognized by cgMLST and cgSNP, illustrating that these two methods are valuable in defining outbreaks and transmission events. All tested isolates were susceptible to vancomycin and meropenem. The rates of resistance to metronidazole, penicillin, cefoxitin, moxifloxacin, and chloramphenicol were low (metronidazole: 1.08%; penicillin: 9.68%; cefoxitin: 0.54%; moxifloxacin: 6.45%; and chloramphenicol: 3.76%). Interestingly, 49.66% of human origin were clindamycin-resistant, and 18.2% were penicillin-insensitive. Importantly, the portion of MDR isolates was significantly lower than in previous reports. The study provides an overview of the epidemiological characteristics of C. perfringens with different origins and hosts in China. C. perfringens demonstrated remarkable genetic diversity and distinct molecular features compared to antibiotic-resistance profiles from other studies.